(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
Hydroxyapatite Ca10(PO4)6(OH)2 is a significant component of bone and tooth structure, and it is considered a biologically distinct material, making it suitable for use in bone implants. It also plays an important role in treating pollution, especially water pollution with pollutants such as heavy metals. In this research, the hydroxyapatite compound was prepared by a wet chemical precipitation method depending on a natural biological source (egg shells) that contains a large amount of calcium carbonate, and the nature of the resulting material was ascertained by using infrared spectroscopy (FTIR) where the peaks indicated at wavelengths, 489.831, 606.503, 1049.09 cm-1 on the presence of phosphates (PO4-3) and the peak at 3568.63 cm-1 on the presence of hydroxyl groups. Also, an atomic force microscope (AFM) was used to measure the dimensions of the material, and it was found that the average dimensions of the hydroxyapatite grains were about 40-60 nm.